PERAN ORANG TUA PADA IBU USIA MUDA DALAM MENANAMKAN NILAI-NILAI KARAKTER ANAK USIA DINI DI POS PAUD ADHI SIWI KELURAHAN CANDI SEMARANG - Rika Nur Afriani; Mintarsih Arbarini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
In the era of globalization and advances in digital technology, the role of parents in instilling character values ​​in early childhood is crucial. Children now grow up in an information-rich environment, a culture of instant gratification, and the influence of the digital world, which can influence moral values. Attitudes and characteristics of early childhood are influenced by the ongoing role of parents, especially young mothers aged 15-49 years or couples of childbearing age (PUS). This research is a descriptive study using a qualitative approach, which reveals facts, phenomena, and conditions that occurred during the research in the field and presents data as they are. The subjects of this study were early childhood children at the Adhi Siwi Early Childhood Education Post in Candi Village. Data collection techniques used were observation, interviews, and documentation. The results of the study revealed the role of parents, especially young mothers aged 15-49 years, as the first and primary educators who play a crucial role in instilling character in children. Parents' role in carrying out their duties also faces various obstacles or underlying factors, but behind all of this, parents still see success achieved when they have successfully taught their children and instilled character values ​​in them as early as possible. The conclusion of this study is that young mothers have taught and implemented character values ​​to their children from an early age in various ways, and continue to carry out their roles well despite several similar inhibiting factors.